Redesign Of Brawijaya Terminal, Banyuwangi, Using A Sustainable Architecture Approach - Muhamad Wahyudi; Luhut Indra; S. Wardiningsih; Yudha Kartika (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Banyuwangi has continued to develop as a major tourism destination, increasing the need for adequate transportation infrastructure. Brawijaya Terminal, a Type-B facility serving intercity and local routes, is currently limited by fragmented building layouts, inefficient circulation, insufficient passenger facilities, and a lack of cultural and environmental responsiveness. These issues highlight the need for a redesign that improves performance while integrating sustainable architectural principles and local identity. This study uses a qualitative descriptive method, combining field observations, surveys, documentation, and literature review. The analysis focused on spatial organization, circulation patterns, microclimate, vegetation, and user needs. Findings show that overlapping circulation between buses, minibuses, private vehicles, and pedestrians reduces safety and efficiency. Poor building orientation limits natural lighting and ventilation, creating uncomfortable thermal conditions. Green open space is insufficient to support microclimate and rainwater absorption. The redesign applies principles of sustainable architecture, including compact massing, improved orientation, natural ventilation, renewable energy, rainwater harvesting, and the use of local materials. Green areas, permeable surfaces, and shaded pedestrian corridors support environmental performance and user comfort. Semi-open waiting areas and accessible circulation improve passenger experience, while Osing cultural elements reinforce local identity. The results demonstrate that applying sustainable design can improve environmental performance, circulation efficiency, and cultural expression in public infrastructure. The redesigned Brawijaya Terminal offers a functional, comfortable, and contextually meaningful facility that can serve as a model for sustainable transportation development in Indonesia.